Loss of α-Calcitonin Gene-Related Peptide (αCGRP) Reduces Otolith Activation Timing Dynamics and Impairs Balance - Jones, Sherri M.; Vijayakumar, Sarath; Dow, Samantha A.; Holt, Joseph C.; Jordan, Paivi M.; Luebke, Anne E. (Frontiers in Molecular Neuroscience, 2018)
Calcitonin-gene related peptide (CGRP) is a neuroactive peptide that is thought to play a role at efferent synapses in hair cell organs including the cochlea, lateral line, and semicircular canal. The deletion of CGRP in transgenic mice is associated with a significant reduction in suprathreshold cochlear nerve activity and vestibulo-ocular reflex (VOR) gain efficacy when compared to littermate controls. Here we asked whether the loss of CGRP also influences otolithic end organ function and contributes to balance impairments. Immunostaining for CGRP was absent in the otolithic end organs of αCGRP null (-/-) mice while ChAT immunolabeling appeared unchanged suggesting the overall gross development of efferent innervation in otolithic organs was unaltered. Otolithic function was assessed by quantifying the thresholds, suprathreshold amplitudes, and latencies of vestibular sensory evoked potentials (VsEPs) while general balance function was assessed using a modified rotarod assay. The loss of αCGRP in null (-/-) mice was associated with: (1) shorter VsEP latencies without a concomitant change in amplitude or thresholds, and (2) deficits in the rotarod balance assay. Our findings show that CGRP loss results in faster otolith afferent activation timing, suggesting that the CGRP component of the efferent vestibular system (EVS) also plays a role in otolithic organ dynamics, that coupled with reduced VOR gain efficacy, impairs balance.